In Vitro Assessment of Estrogenic Potential of Biofield Energy Treatment using Human Endometrial Adenocarcinoma Cell Line - Mahendra, Kumar Trivedi; Snehasis, Jana (Journal of Women's Reproductive Health, 2018)
The objective of the study was to investigate the effect of Consciousness Energy Healing based DMEM medium on the level of alkaline phosphatase enzyme (ALP) activity in Ishikawa cells. The test item, DMEM medium was divided into two parts. One part of the test item received Consciousness Energy Healing Treatment by a renowned Biofield Energy Healer, Mahendra Kumar Trivedi and was labeled as the Biofield Energy Treated DMEM, while the other part did not receive any treatment, and defined as the untreated DMEM group. The cell viability using MTT assay of the Biofield Energy Treated DMEM group was observed as 108%, which indicated that the test item was safe and non-toxic. The estrogenic potential using ALP level showed a significantly increase by 73.21% in the Biofield Energy Treated DMEM group as compared to the untreated DMEM group. Overall, the experimental data suggested that the Biofield Energy Treated DMEM has significantly improved ALP level, which play a vital role for the promotion and maintenance of estrogen level. Based on the study outcomes, it is concluded that Biofield Energy Healing Treatment showed a significant improved ALP level, which can be used in various estrogenic disorders such as hypophosphatasia, osteoporosis, severe anemia, malnutrition, hypothyroidism, magnesium deficiency, heart surgery, aplastic anemia, chronic myelogenous leukemia, enteritis in children, Wilson’s disease, pernicious anemia, bacterial infection and intrauterine infection is a leading cause of pelvic inflammatory disease, subfertility, infertility, endometritis, early pregnancy loss, fetal defects, and preterm birth.
Keywords: Biofield Energy; ALP; Estrogenic potential; Ishikawa cell; DMEM; Menstrual disorder